2023
DOI: 10.1183/23120541.00317-2022
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and its continuing burden after 12 months: a longitudinal observational prospective multicentre trial

Abstract: BackgroundRecovery trajectories from coronavirus disease 2019 (COVID-19) call for longitudinal investigation. We aimed to characterise the kinetics and status of clinical, cardiopulmonary and mental health recovery up to 1 year following COVID-19.MethodsClinical evaluation, lung function testing (LFT), chest computed tomography (CT) and transthoracic echocardiography were conducted at 2, 3, 6 and 12 months after disease onset. Submaximal exercise capacity, mental health status and quality of life were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…A total of 2517 studies were identified, of which 43 met the inclusion (N = 8858 patients) ( Figure 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. The majority of studies were from China (14 studies [ 51 , 58 , 59 , 60 , 61 , 64 , 65 , …”
Section: Resultsmentioning
confidence: 99%
“…A total of 2517 studies were identified, of which 43 met the inclusion (N = 8858 patients) ( Figure 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. The majority of studies were from China (14 studies [ 51 , 58 , 59 , 60 , 61 , 64 , 65 , …”
Section: Resultsmentioning
confidence: 99%
“…Approximately 1 year after infection, different studies report frequencies ranging from 40% to as high as 65%. 3,5,16 According to Van Wambeke et al, 90% of post-COVID patients reported fatigue as a lingering symptom at the 15-month mark following infection. 15 Furthermore, according to a recent meta-analysis, 52.6% of hospitalized patients had at least one symptom after 126 days, with fatigue, pain or discomfort, sleep disturbances, dyspnea and restricted usual activity being the five most common symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…27 One of the most often impacted elements is mental health. 16 Regardless of disease severity and despite the fact that most COVID-19 survivors resume their old way of life, they exhibit a markedly worse QoL and health status. 5 Regarding vaccination status, we did not find any substantial correlation between vaccinated or unvaccinated patients or the number of doses received with the persistence of symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These challenges have been typically assessed through symptom checklists[5], generic measures such as the PHQ-9 and GAD-7, and generic health-related quality of life measures like the EQ-5D. [6–8]…”
Section: Introductionmentioning
confidence: 99%